Estudo da ação da glândula adrenal no desenvolvimento da hiperalgesia muscular crônica difusa - Freitas, Camila Evelyn Perete de (2021)
Considered a rare clinical condition and difficult to treat, chronic pain is described as a cognitive-emotional sensation of durability above what is considered normal. Commonly diagnosed in menopausal women, fibromyalgia, an example of chronic pain, has been studied over the years. Possible hyperexcitability mechanisms of the excitatory pathways sensitive to substance P and glutamate are speculated as a possible cause of the development of the syndrome, so called because it triggers several associated symptoms such as sleep disturbances, joint pain, anxiety and depression. Futhermore, it is presumed that functional changes in Hypothalamus-hypophysis-adrenal axis (HPA axis) could contribute with mechanisms of chronic pain, although it is not clear how. Previous studies have already pointed out the influence of gland modulation, especially glucocorticoids, on the neuropathic nociceptive response. In patients with fibromyalgia, a reduction in glucocorticoid receptors in peripheral defense cells was observed. However, it is not clear how much the functional changes in this gland can interfere with hyperalgesia. Therefore, the present study aims to evaluate the influence of corticosteroids on adrenalectomized rats with chronic and diffuse hyperalgesia. The animals were divided into 5 (n=6): control group(CTRL); group induced to the fibromyalgia model(FIBRO); SHAM group, bilateral adrenalectomy group (ADX), and 2.5% dexamethasone treated adrenalectomy group (ADX+DEX). The SHAM, ADX and DEX groups were also induced to the fibromyalgia model, with the first injection being administered 5 days after surgery. For the DEX group, dexamethasone was administered at 6 am on the day following the last saline injection(acute), following a protocol of 7 days of injections performed every 12 hours(chronic). For this group, behavioral tests were performed after the first injection (Day 6) and after all injections (Day 13). Behavioral analysis was performed on day 6 (acute) and day 13 (chronic). The acute data collected were analyzed by the t test, for chronic and intergroup, one-way and two-way ANOVA, respectively, followed by Bonferroni post-test (p<0.05). There was reduction in the distance walked only on the ADX+DEX in the complete treatment with dexamethasone. Likewise, thermal latency was lower for the group, both for acute and chronic treatment. The paw removal threshold was lower for both the left and right paws for the animals of the groups: FIBRO, SHAM and ADX+DEX, again in both treatments. The results confirm the influence of the adrenal gland in modulating diffuse chronic muscle hyperalgesia, since adrenalectomized animals did not show hyperalgesic response when compared to the control group. Our data suggest that both acute and chronic dexamethasone treatment was not effective in reversing the chronic hyperalgesia. On the contrary, chronic treatment with dexamethasone promotes a more accentuated state of hyperalgesia, which demonstrates the direct participation of the adrenal gland in the development of fibromyalgia.